1986
DOI: 10.1002/art.1780290206
|View full text |Cite
|
Sign up to set email alerts
|

Nailfold capillary microscopy in mixed connective tissue disease. Comparison with systemic sclerosis and systemic lupus erythematosus

Abstract: Nailfold capillary microscopy patterns in 22 patients with mixed connective tissue disease (MCTD) were compared with those of 21 patients with systemic lupus erythematosus (SLE) and 30 patients with systemic sclerosis (scleroderma [SD]). Microvascular data were classified blindly as follows: normal, nonspecific abnormalities, SD pattern, and SLE pattern, with special attention to the presence of dystrophic, branched "bushy" capillary formations. Of the 22 patients with MCTD, 63.6% had an SD pattern, 22.7% had … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
29
0
4

Year Published

1991
1991
2013
2013

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(37 citation statements)
references
References 21 publications
4
29
0
4
Order By: Relevance
“…No abnormalities were noted on renal angiogram. Fingernail capillaroscopy indicated that 90% of patients with MCTD had the same pattern of capillary dilation and drop-out as has been reported in SSc (42). In another study, all patients had abnormal nailfold capillaries with patterns similar to those seen in SSc (42).…”
Section: Cardiovascular Involvementsupporting
confidence: 53%
“…No abnormalities were noted on renal angiogram. Fingernail capillaroscopy indicated that 90% of patients with MCTD had the same pattern of capillary dilation and drop-out as has been reported in SSc (42). In another study, all patients had abnormal nailfold capillaries with patterns similar to those seen in SSc (42).…”
Section: Cardiovascular Involvementsupporting
confidence: 53%
“…According to these authors, abnormalities consisted of elongated and tiny loops, microhemorrhages, low capillary density, and subpapillary venous plexus visibility alterations. Although they did not seem to be pathognomonic for RA, they do appear to be sufficiently characterised as to differentiate patients with RA from normal controls (34)(35)(36)(37)(38). The hypotheses on the pathogenic mechanism of vascular damage involve the autoantibody and circulating immune complex precipitation in the vessel walls, considered to be the main cause of damage.…”
Section: Oral Capillaroscopy and Autoimmune Pathologiesmentioning
confidence: 99%
“…5,14,15 Nailfold abnormalities constituting an SD pattern have also been demonstrated in 54% to 64% of patients with MCTD, 5,16 in 83% of patients with dermatomyositis, 17 and in only 2.0% to 4.8% of patients with SLE. 5,16 In SLE and dermatomyositis, nonspecific abnormal findings were observed in 24.0% and 13.6% of the patients, respectively, and an "SLE capillaroscopic pattern," defined as torturous meandering capillaries and a prominent subpapillary plexus, was noted in 57.0% and 22.7% of the patients, respectively. 16,18 A recent study using an optical microscope and a video camera with a 60-to 240-fold magnification demonstrated an SD pattern in only 43% of patients with scleroderma and some capillary abnormalities short of an SD pattern in 5% to 15% of the normal controls.…”
Section: Commentmentioning
confidence: 99%